Wpływ myśli feministycznej na zmiany współczesnego prawa - szkic problemu - Jedlecka, Wioletta (Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego, 2015)
A purpose of this article is presenting the influence of the feminism on changes to the law. It is hard to find the unabridged and explicit definition of the feminism in literature. J. Hannam is using the term “feminism” to determining the idea for opposing inequalities between women and men. Activities of women’s movements in the world fighting for the gender equality in the economic, political and social life, they are leading to the regulation these matters in the international law and in the European law. The principle of the equality between women and men is regarded as the basic Community law. Although it can seem that the woman is equal to man, however it isn’t still finding expression in the real life
Keywords: feminism; gender; unequality; emancipation; law; private sphere; public sphere